The Effect of Side of Implantation on the Cortical Processing of Frequency Changes in Adult Cochlear Implant Users - Liang, Chun; Wenstrup, Lisa H.; Samy, Ravi N.; Xiang, Jing; Zhang, Fawen (Frontiers in Neuroscience, 2020)
Abstract: A cochlear implant (CI) is widely used in children and adults to restore hearing function. However, CI outcomes are largely various. The affected factors have not been well understood. It is well known that the right and left hemispheres play different roles in auditory perception in adult normal hearing listeners. It is unknown how the implantation side may affect the outcomes of CIs. In this study, the effect of the implantation side on how the brain processes frequency changes within a sound was examined in 12 right-handed adult CI users. The outcomes of CIs were assessed with behaviorally measured frequency change detection threshold (FCDT), which has been reported to significantly affect CI speech performance. The brain activation and regions were also examined using acoustic change complex (ACC, a type of cortical potential evoked by acoustic changes within a stimulus), on which the waveform analysis and the standardized low-resolution brain electromagnetic tomography (sLORETA) were performed. CI users showed activation in the temporal lobe and non-temporal areas, such as the frontal lobe. Right-ear CIs could more efficiently activate the contralateral hemisphere compared to left-ear CIs. The increase in the activation in the left temporal lobe together with the decreased activation in the left frontal lobe was correlated with good performance of frequency change detection (lower FCDTs). Such a trend was not found in right-ear CIs. These results suggest that the implantation side may significantly affect neuroplasticity patterns in adults.